Production and characterisation of Al-Mg-Cr alloy for machine tool applications (2020)
Industrialisation and technological advancement are immensely influenced by materials development and innovation. Recent studies have shown that the use of some specialised alloying elements can be explored for enhancing properties of monolithic alloys. This study focuses on the production and characterisation of Al-Mg-Cr alloy suitable for machine tool applications. Al-Mg-Cr alloy was developed using sand mould and two-step stir-casting method. Chromium was added to Al-Mg alloy at varying contents of 0.5, 1.0, 1.5 and 2.0 %. Tensile tests were carried out in accordance with ASTM E8 to determine ultimate tensile strength (UTS), percentage elongation and modulus of elasticity at varying chromium contents. The evolved microstructures were examined using an optical microscope (OPM). The study revealed that the alloy containing 1.5% chromium exhibited maximum ultimate tensile strength of 135.15 MPa and percentage elongation of 3.76 %. However, Al-Mg-Cr alloy containing 1.0% chromium exhibited best combination of UTS (123.98 MPa), percentage elongation (3.32%), modulus of elasticity (12.11 GPa) and microstructural features. Five samples of Al-Mg-1.0Cr alloy were thereafter heat treated at different temperatures from 250 ˚C to 450 ˚C. The heat treated samples were also subjected to tensile tests and optical microscopy. The results were compared with the as-cast Al-Mg-1.0Cr alloy. The results showed that heat treatment of Al-Mg-Cr alloy had adverse effect on their mechanical and microstructural properties. The outcome of this study has shown that chromium as alloying element has potentials for enhancing tensile and microstructural characteristics of Al-Mg based alloys, and the benefit can be explored for machine tool applications.